Pengaruh Store Atmosphere dan Harga Terhadap Keputusan Pembelian Konsumen Pada Warunk Upnormal Jambi - Indra Gunawan (Jurnal Dinamika Manajemen, 2020)
The purpose of this study was to analyze the effect of Store Atmosphere and price on purchasing decisions at Warunk Upnormal Jambi both simultaneously and partially and to analyze the dominant factors on purchasing decisions at Warunk Upnoral Jambi. The method used in this study is a quantitative method using the SPSS analysis tool to test multiple linear regression. The results of the study concluded that Store atmosphere had a significant positive effect on purchasing decisions (case study on Warunk Upnormal Jambi), prices had a significant negative effect on purchasing decisions (case study on Warunk Upnormal Jambi) and Store Atmosphere and Price had a simultaneous effect on purchasing decisions (case Keywords: study at Warunk Upnormal Jambi).